Malware forensics field guide for Windows systems : digital forensics field guides - Malin, Cameron H.; Casey, Eoghan ;Aquilina, James M.;Rose, Curtis W. (Waltham, MA : Syngress, 2012)
Dissecting the dark side of the Internet with its infectious worms, botnets, rootkits, and Trojan horse programs (known as malware) is a treaterous condition for any forensic investigator or analyst. Written by information security experts with real-world investigative experience, this book contains checklists for specific tasks, case studies of difficult situations, and expert analyst tips.
Malware incident response -- Memory forensics -- Post-mortem forensics -- Legal considerations -- File identification and profiling -- Analysis of a malware specimen.
Includes bibliographical references and index.
Keywords: MICROSOFT WINDOWS (COMPUTER FILE)